SISTEM PINTAR KONTROL AIR CONDITIONER (AC) BERBASIS FUZZY LOGIC DAN PENGARUHNYA PADA KONSUMSI ENERGI LISTRIK - Palallo, Tomas; Amin, Nurhani; Arifin, Yusnaini; Sholihah, Ratih mar'atus; Mahmudi, Irwan (Foristek, 2025)
The manual use of Air Conditioners (AC) often leads to excessive electricity consumption, as temperature settings are not adjusted to actual environmental conditions. This study aims to design and implement an AC control system based on Mamdani fuzzy logic to automatically regulate room temperature according to thermal comfort standards, as well as to analyze its effect on electricity consumption. The system was developed using four DHT11 sensors connected to an ESP32 microcontroller as the main controller, while energy consumption was monitored using a PZEM-004T sensor and transmitted to the ThingSpeak platform. Experimental results show that the fuzzy logic-based control system was able to adaptively adjust the AC temperature with high accuracy. The application of the system resulted in an energy consumption of 5.01 kWh over three days, compared to 8.87 kWh under manual control. Thus, the system achieved energy savings of 3.86 kWh or 43.82%. These findings demonstrate that applying fuzzy logic to AC control is effective in improving energy efficiency and supporting electricity cost reduction.